2019
DOI: 10.1017/s1355617719000626
|View full text |Cite
|
Sign up to set email alerts
|

Use It or Lose It? A 5-Year Follow-up Study of Goal Management Training in Patients with Acquired Brain Injury

Abstract: Objectives:To determine the perceived 5-year outcome of Goal Management Training (GMT) for individuals with chronic acquired brain injury and executive dysfunction, when compared to a nonspecific psychoeducational intervention (Brain Health Workshop, BHW).Methods:Of the 67 subjects in the initial randomized controlled trial [Tornås et al. (2016). Journal of the International Neuropsychological Society, 1–17], 50 (GMT, n = 21; BHW, n = 29) subjects returned written consent and questionnaires (54% male, age 45.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Further, results suggest that these improvements are specific to GMT, and as such provide preliminary support of strategy-based CR being more effective in producing longterm improvements in mental health. Changes in perceived everyday EF did not sustain over the course of years in the present study, like previous evaluations of long-term effects following GMT (15). Concurrently, our findings align with previous research failing to find evidence of different longterm effectiveness between treatments (10,11).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Further, results suggest that these improvements are specific to GMT, and as such provide preliminary support of strategy-based CR being more effective in producing longterm improvements in mental health. Changes in perceived everyday EF did not sustain over the course of years in the present study, like previous evaluations of long-term effects following GMT (15). Concurrently, our findings align with previous research failing to find evidence of different longterm effectiveness between treatments (10,11).…”
Section: Discussionsupporting
confidence: 88%
“…Overall, these findings align with a recent meta-analysis including various neurocognitive disorders concluding that GMT is moderately effective in improving EFs and aspects of mental health (14). Nevertheless, only one study has reported follow-up analyses more than 2 years following GMT (15). Here, our research group found that improvements following GMT in EF and quality of life at 6-months follow-up, were no longer present at 5-years follow-up (15)(16)(17).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…The standardized manual ensures fidelity and allows for efficient training of clinicians. Future studies should assess maintenance of strategies learnt during GMT [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future research should also include objective functional measures (e.g., school performance) and combinations of assessment levels to further clarify the indexed constructs. Finally, future research may consider examining treatment dose (e.g., number of sessions and total treatment time) and the potential effects of “booster sessions” [ 91 ].…”
Section: Discussionmentioning
confidence: 99%